2007
DOI: 10.1007/s00284-007-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses and Proteomic Analysis of Escherichia coli Exposed to Green Tea Polyphenols

Abstract: The purpose of this study was to characterize the cellular response and proteomic analysis of Escherichia coli exposed to tea polyphenols (TPP) extracted from Korean green tea (Camellia sinensis L). TPP showed a dose-dependent bactericidal effect on E. coli. Analysis of cell-membrane fatty acids of E. coli cultures treated with TPP identified unique changes in saturated and unsaturated fatty acids, whereas scanning electron microscopic analysis demonstrated the presence of perforations and irregular rod forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…On the other hand, Ikigai et al reported that catechins primarily act on and damage bacterial membranes [13]. In a recent study, we reported that TPP-treated E. coli had unique changes in saturated and unsaturated fatty acids in their cell membranes, further supporting the impact of TPP on membranes [6]. These studies illustrate that TPP may have multiple mechanisms of antibacterial activity, which can synergize the bactericidal activity of various antibiotics.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, Ikigai et al reported that catechins primarily act on and damage bacterial membranes [13]. In a recent study, we reported that TPP-treated E. coli had unique changes in saturated and unsaturated fatty acids in their cell membranes, further supporting the impact of TPP on membranes [6]. These studies illustrate that TPP may have multiple mechanisms of antibacterial activity, which can synergize the bactericidal activity of various antibiotics.…”
Section: Resultsmentioning
confidence: 72%
“…Recently, we investigated the antibacterial effects of TPP on E. coli as well as proteomic changes induced by exposure to TPP [6]. In the present study, we examined the antibacterial and synergistic activities of TPP on 13 clinical isolates of MRSA, and comparative proteomic analysis was performed to elucidate the proteins expressed in MRSA exposed to TPP.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that certain extracts of antioxidant tea inhibitors inhibit some food-borne pathogenic microorganisms such as Bacillus cereus (Almajano et al, 2008;Si et al, 2006), Staphylococcus aureus Si et al, 2006;Taguri et al, 2004), Vibrio cholerae (Taguri et al, 2004), Listeria monocytogenes Si et al, 2006), Escherichia coli (Cho et al, 2007;Si et al, 2006), Salmonella typhimurium (Si et al, 2006), Salmonella enteritidis , Micrococcus luteus y Pseudomona aeruginosa (Almajano et al, 2008); and that in particular green tea catechins may decrease the resistance of S. aureus to antibiotics such as oxacillin (Stapleton et al, 2004).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Proteomic analyses have increased our understanding of chemical-induced stress proteins in bacteria such as Acinetobater, Burkholderia, Pseudomonas, and Escherichia [5][6][7][8]. Recently, we investigated the antibacterial effects of green tea polyphenols (TPP) on methicillin-resistant Staphylococcus aureus (MRSA) and E. coli and the proteomic changes induced by exposure to TPP in these bacteria [9,10]. Although there have been several reports that evaluated the antibacterial effects of the rose flower extract against several bacteria [11,12], we are unaware of any published studies on the cellular and proteomic responses of clinical isolates exposed to the rose flower extract.…”
Section: Introductionmentioning
confidence: 99%